Hubungan Beban Kerja Mental dan Kelelahan Kerja dengan Unsafe Action pada Pengemudi Batik Solo Trans (BST) Koridor 1 - Apri Fadhillah Maharani Sunarno Putri; Ratna Fajariani; Sri Haryati (Journal of Applied Agriculture, Health, and Technology, 2023)
Batik Solo Trans bus corridor 1 is a corridor that serves the longest route with a distance of ±54 km and 121 stops. Secondary data shows an increase in the incidence of BST accidents by 8 cases (18%) in 2022 with 43 cases. The type of accident was dominated by unsafe action as many as 26 cases (60%) and 8 cases (30%) of which occurred in corridor 1. This study aimed to analyze the relationship between mental workload and work fatigue with unsafe action in BST corridor 1 drivers. Respondents were taken from BST corridor 1 drivers with a population and sample of 64 people. The sampling technique uses total sampling. The study used questionnaires to measure mental workload, fatigue, and unsafe action. Data analysis techniques in this study are pearson product-moment test for bivariate analysis and the multiple linear regression test for multivariate analysis. The correlation test results obtained p = 0.000 and r = 0.661, meaning that there is a meaningful and significant relationship between mental workload and unsafe action. The correlation test of the work fatigue variable with unsafe action also showed an important relationship between the two with p = 0.000 and r = 0.640 values. Based on multiple linear regression tests, a significance value of 0.000 was obtained, which means that mental workload and work fatigue together affect unsafe action with a contribution of 53% and fatigue is the most influential variable on unsafe action in BST corridor 1 drivers.